Association between diabetes and subsequent Parkinson disease: A record-linkage cohort study. (10th July 2018) - De Pablo-Fernandez, Eduardo; Goldacre, Raph; Pakpoor, Julia; Noyce, Alastair J.; Warner, Thomas T.
Abstract : Objective: To investigate the association between type 2 diabetes mellitus (T2DM) and subsequent Parkinson disease (PD). Methods: Linked English national Hospital Episode Statistics and mortality data (1999–2011) were used to conduct a retrospective cohort study. A cohort of individuals admitted for hospital care with a coded diagnosis of T2DM was constructed, and compared to a reference cohort. Subsequent PD risk was estimated using Cox regression models. Individuals with a coded diagnosis of cerebrovascular disease, vascular parkinsonism, drug-induced parkinsonism, and normal pressure hydrocephalus were excluded from the analysis. Results: A total of 2, 017, 115 individuals entered the T2DM cohort and 6, 173, 208 entered the reference cohort. There were significantly elevated rates of PD following T2DM (hazard ratio [HR] 1.32, 95% confidence interval [CI] 1.29–1.35; p < 0.001). The relative increase was greater in those with complicated T2DM (HR 1.49, 95% CI 1.42–1.56) and when comparing younger individuals (HR 3.81, 95% CI 2.84–5.11 in age group 25–44 years). Conclusions: We report an increased rate of subsequent PD following T2DM in this large cohort study. These findings may reflect shared genetic predisposition and/or disrupted shared pathogenic pathways with potential clinical and therapeutic implications.